OECS Ports : An Efficiency and Performance Assessment - Cubas, Diana; Briceno-Garmendia, Cecilia; Bofinger, Heinrich C. (World Bank Group, Washington, DC, 2015)
Handling charges in Caribbean ports are two to three times higher than in similar ports in other regions of the world. In some cases, it costs significantly less to ship a container to Hong Kong SAR, China, or Europe than it does to ship to a neighboring island no more than 100 miles away. The reasons for high port-handling costs are linked to procedural inefficiencies along the logistics chain, high freight rates that shipping lines attribute to empty backhauls, and the poor performance of port management and operations. The Organization of Eastern Caribbean States shares the larger Caribbean region's advantages, challenges, and concerns related to the performance of port management and operations. Yet performance assessments have been difficult to make because of data constraints. This report seeks to provide such an assessment along four distinct policy dimensions: (i) traffic development, (ii) the institutional and regulatory framework, (iii) infrastructure development, and (iv) performance, including pricing and finance issues. The report concludes by benchmarking the efficiency of Organization of Eastern Caribbean States ports against other Latin American ports using a stochastic frontier approach, and providing a list of next steps for further research and policy prioritization. To make the current analysis possible, a rigorous exercise in the collection of primary data was conducted, using standardized templates adapted specifically to the Organization of Eastern Caribbean States context. The collection of data proved to be particularly difficult on financial and performance metrics, since many of the ports lack strong statistical systems and institutions.